ANALISIS YURIDIS PENEGAKAN HUKUM PADA PELAKU PREDATORY PRICING DI APLIKASI E-COMMERCE DITINJAU MENURUT UNDANG- UNDANG NO 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Hasanah, Amalia (At-Tanwir Law Review, 2024)
As the digital world develops, it causes changes in the trading system in the world, one of which is in Indonesia. The emergence of trade carried out indirectly between sellers and buyers on e-commerce platforms. With the development of this trading system, transactions can be made easier because there is no need to meet face to face, but there are also problems that arise, such as unhealthy business competition. One example is predatory pricing or selling at a loss, where they sell products below the capital price or below the production price which is expected to beat rivals with similar products on a digital platform. Usually these business actors offer promotions that are as attractive as possible so that consumers or the public are interested in increasing their shopping in e-commerce. This requires strong law enforcement so that predatory pricing does not become a culture in digital business and harms many business actors. This research will discuss how to regulate and enforce the law against perpetrators of predatory pricing in e-commerce applications in terms of Law Number 5 of 1999 concerning the Prohibition of Monopolies and Unfair Business Competition. This research uses a normative legal approach. The results of this research show that business actors who are proven to have carried out predatory pricing practices have violated Article 20 of Law Number 5 of 1999 concerning the Prohibition of Monopoliesand Unfair Business Competition and can be subject to administrative or criminal sanctions.